Assessment of toxic heavy metals concentrations in soils and wild and cultivated plant species in Limni abandoned copper mining site, Cyprus - Christou, Anastasis; Theologidis, Christodoulos; Costa, Costas; Kalavrouziotis, Ioannis K.; Varnavas, Soterios P. (My University, 2017)
Mine tailings represent a serious source of soil pollution with public health implications. The objectives of this study were(1) to assess the level of toxic and heavy metal mobilization from the tailing spoil-heap of Limni abandoned mine at Cyprus and the extent of soil contamination to the surrounding area by using pollution indicators; (2) to investigate the uptake and accumulation of heavy metals by cultivated crops; and (3) to estimate the potential of native wild plant species grown in the studied area to be used in phytomanagement approaches. The tailing spoil heap exhibited significantly higher S, Zn, Cu and Pb concentrations compared to the ones found in control reference samples (RS). The lateral mobilization of Mg, S, Zn, Cu and Pb resulted to the contamination of the tailing surrounding areas with these metals. Moreover, Mn and Cu concentrations in the tailing and the surrounding areas exceeded the MPLs for agricultural soils. The severe to very severe pollution of the tailing surrounding sides with S, Zn and Cu was also evident by the calculated values of enrichment factor and geoaccumulation index. The values of combined pollution index also uncovered the extremely high pollution of the tailing and the moderate pollution of the surrounding sites with all analyzed elements. The concentration of Cd in fig, peanut and lemon fruits, as well as in the grains and straw of barley exceeded MPLs, highlighting the potential Cd-mediated hazardous effects from the consumption of these produces. The examination of heavy metal content in wild native plant species showed that Inula viscosa L. has the potential to be used for the phytostabilization of Cd and Pb, and Allium ampeloprasum L. for the phytostabilization of Pb. Overall, results suggest that the Limni mine tailing and its surrounding sites are highly polluted; thus agricultural activity in the studied area should be prohibited and phytomanagement should be urgently carried out.
Keywords: Enrichment factor; Geoaccumulation index; Heavy metal; Phytomanagement; Soil pollution; Tailing